Development of a spiral spin‐ and gradient‐echo (spiral‐SAGE) approach for improved multi‐parametric dynamic contrast neuroimaging. Issue 6 (20th July 2021) - Stokes, Ashley M.; Ragunathan, Sudarshan; Robison, Ryan K.; Fuentes, Alberto; Bell, Laura C.; Karis, John P.; Pipe, James G.; Quarles, C. Chad
Abstract : Purpose: The purpose of this study was to develop a spiral‐based combined spin‐ and gradient‐echo (spiral‐SAGE) method for simultaneous dynamic contrast‐enhanced (DCE‐MRI) and dynamic susceptibility contrast MRI (DSC‐MRI). Methods: Using this sequence, we obtained gradient‐echo TEs of 1.69 and 26 ms, a SE TE of 87.72 ms, with a TR of 1663 ms. Using an iterative SENSE reconstruction followed by deblurring, spiral‐induced image artifacts were minimized. Healthy volunteer images are shown to demonstrate image quality using the optimized reconstruction, as well as for comparison with EPI‐based SAGE. A bioreactor phantom was used to compare dynamic‐contrast time courses with both spiral‐SAGE and EPI‐SAGE. A proof‐of‐concept cohort of patients with brain tumors shows the range of hemodynamic maps available using spiral‐SAGE. Results: Comparison of spiral‐SAGE images with conventional EPI‐SAGE images illustrates substantial reductions of image distortion and artifactual image intensity variations. Bioreactor phantom data show similar dynamic contrast time courses between standard EPI‐SAGE and spiral‐SAGE for the second and third echoes, whereas first‐echo data show improvements in quantifying T1 changes with shorter echo times. In a cohort of patients with brain tumors, spiral‐SAGE–based perfusion and permeability maps are shown with comparison with the standard single‐echo EPI perfusion map. Conclusion: Spiral‐SAGE provides a substantial improvement for the assessment of perfusion and permeability by mitigating artifacts typically encountered with EPI and by providing a shorter echo time for improved characterization of permeability. Spiral‐SAGE enables quantification of perfusion, permeability, and vessel architectural parameters, as demonstrated in brain tumors.